Postmortem sampling time effect on toxicity biomarkers in rats exposed to an acute lethal methomyl dose - Shreen D. Nusair; Mohammad Ananbeh; Aref Zayed; Mohammad I. Ahmad; Nidal A. Qinna (Toxicology Reports, 2022)
Regulations often are imposing long postmortem times before autopsy leading to certain toxicity-unrelated changes in biomarkers, which in turn may affect the reliability of toxicity evaluation during forensic investigations. Since methomyl pesticide shows significant toxicity and is frequently encountered in poisoning cases, the current study evaluated different parameters in methomyl intoxicated rats at three different postmortem intervals (Hour 0, Hour 3 and Hour 6). Eighteen adult Sprague Dawley rats were poisoned with methomyl to simulate actual methomyl poisoning cases. The time of death was assigned as Hour 0. The animals were divided into 3 groups (n = 6) to collect blood and tissue samples at the selected time points. Body weight, relative organ weight, protein concentration, methomyl concentration and acetylcholinesterase activity (AChE) were assessed in blood and different tissues (liver, spleen, kidney, brain, eye, and bone marrow) to evaluate the effect of postmortem sampling time. Outcomes revealed significant decreases in methomyl concentration in blood and bone marrow with advanced sampling time (P < 0.001). Similarly, there were significant reductions in AChE activity in the kidney (P < 0.01), while the enzyme activity significantly increased in brain samples (P < 0.05). Findings illustrated the importance of sampling time in toxicity studies because it could alter experimental results and impact consequent interpretations, as well as it may alter postmortem biomarkers in related forensic cases.